2006
DOI: 10.1128/jcm.00154-06
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis Virulent Plasmid pX02 Genes Found in Large Plasmids of Two Other Bacillus Species

Abstract: In order to cause the disease anthrax, Bacillus anthracis requires two plasmids, pX01 and pX02, which carry toxin and capsule genes, respectively, that are used as genetic targets in the laboratory detection of the bacterium. Clinical, forensic, and environmental samples that test positive by PCR protocols established by the Centers for Disease Control and Prevention for B. anthracis are considered to be potentially B. anthracis until confirmed by culture and a secondary battery of tests. We report the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 24 publications
2
50
0
2
Order By: Relevance
“…The amplification of multiple signature sequences per organism also will reduce false-positive results in complex samples. False positives can be an issue if detection relies on single targets due to the presence of homologous sequences in related organisms or unknown sources when analyzing environmental samples (19,20).…”
mentioning
confidence: 99%
“…The amplification of multiple signature sequences per organism also will reduce false-positive results in complex samples. False positives can be an issue if detection relies on single targets due to the presence of homologous sequences in related organisms or unknown sources when analyzing environmental samples (19,20).…”
mentioning
confidence: 99%
“…The pAM␀1 family of replicons requires transcription into the ori from their rep gene for replication to occur (9). Furthermore, rep gene transcription is regulated by CT-driven attenuation (7,31). We performed Northern blot analysis to identify the repS transcript and/or its attenuated products.…”
Section: Resultsmentioning
confidence: 99%
“…pXO1 and pXO2 plasmids and/or elements have been identified within the genomes of other members of the genus Bacillus [10]. In silico (BLAST) analysis of the pXO1 and pXO2 PCR amplicon sequences indicated that if tested against the B. cereus G9241 strain [8] then a pXO1 positive would result, as would a pXO2 PCR if tested against the B. cereus (var.)…”
Section: Discussionmentioning
confidence: 99%
“…‱ mL -1 (4 cases) and 10 1 cfu ‱ mL -1 (2 cases). Bloods were taken at 12 hour intervals after inoculation and in some cases the onset of bacteraemia was not immediately associated with observable disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation